Governance, sentiment analysis, and initial public offering underpricing (2019)
Research Question/Issue What is the relationship between governance, tone in language, and underpricing of initial public offerings (IPOs) in Latin America? Research Findings/Insights We find a positive (negative) and statistically significant relationship between board size (board independence) and IPO underpricing at the time firms go public. But more importantly, when interacting with corporate governance variables at the firm level, uncertainty in tone still shows statistical significance, which suggests that tone in communications matters for underpricing independently of governance provisions at the firm level. Theoretical/Academic Implications Bigger boards seem to lead to greater underpricing, whereas more independent boards mitigate it. This finding stresses the relevance of functional convergence in regions with weak institutions such as Latin America. Our results also suggest that tone matters for underpricing even in firms with good governance practices. We argue that tone in corporate communications is a strong signaling mechanism for market participants. Practitioner/Policy Implications Our results suggest that tone in firms' communications is relevant for market valuation. In the context of family firms in an underresearched context such as Latin America, we show that reputation effect is priced by the market valuation of the IPO.